1993
DOI: 10.1002/pola.1993.080310418
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nylon 6–clay hybrid by montmorillonite intercalated with ϵ‐caprolactam

Abstract: It was found that montmorillonite was intercalated with ϵ‐caprolactam. X‐ray diffraction revealed that the chain axes of the ϵ‐caprolactam were parallel to the montmorillonite plates. The intercalated montmorillonite was swollen by molten ϵ‐caprolactam at 200°C. ϵ‐Caprolactam and 6‐aminocaproic acid (accelerator) were polymerized with the intercalated montmorillonite at 260°C for 6 h, yielding a nylon 6‐clay hybrid. X‐ray diffraction and transmission electron micrography revealed that the silicate layers of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
563
1
11

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 913 publications
(584 citation statements)
references
References 5 publications
9
563
1
11
Order By: Relevance
“…Indeed increasing the interfacial properties increases the volume of polymer chains influenced. The improvement of the dispersion also increases the average aspect ratio of the nanofillers in the polymer matrix and as a consequence tensile properties are improved as already reported [31] for clay platelets. Here apparently, MWNTs are able to reinforce the PP matrix due to their large aspect ratio combined with high mechanical properties.…”
Section: Mechanical Characterizationsupporting
confidence: 58%
“…Indeed increasing the interfacial properties increases the volume of polymer chains influenced. The improvement of the dispersion also increases the average aspect ratio of the nanofillers in the polymer matrix and as a consequence tensile properties are improved as already reported [31] for clay platelets. Here apparently, MWNTs are able to reinforce the PP matrix due to their large aspect ratio combined with high mechanical properties.…”
Section: Mechanical Characterizationsupporting
confidence: 58%
“…1 They demonstrated that nylon6/clay nanocomposites showed a significant improvement in mechanical and thermal properties. [2][3][4] Since then, much work has been dedicated to polymer nanocomposites. This work has revealed that these nanocomposites show remarkable material property enhancements, including mechanical properties, 5,6 thermal properties 7,8 and gas-barrier properties, 9 compared with the virgin polymers or conventional micro filler-incorporated composites while using only a small amount of nanofillers.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer-clay nanocomposites have been studied extensively for several years, and it is now known that the fire properties, thermal stability [1] and [2], gas barrier properties [3], ionic conductivity [4], mechanical properties [5] and [6], etc., are all improved relative to the virgin polymer. Nanocomposites can be described as immiscible, intercalated or exfoliated depending on the type of dispersion of the nanomaterial in the polymer.…”
Section: Introductionmentioning
confidence: 99%